(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The present work was developed in areas of the organoponic of the Basic Unit of Cooperative Production "Marcial Jiménez" belonging to the Sugar Company "Enidio Diaz Machado" located in the municipality of Campechuela, Granma province. An experiment was set up after transplantation in order to evaluate the application of different doses of Bayfolan Forte® in the cultivation of Lettuce (Lactuca sativa, L) and to establish the most effective dose in the agronomic indicators and the agroproductive performance of the cultivar Black Seeded Simpson in the period from December 14, 2019 to January 11, 2020, five treatments were evaluated, in random blocks and three replications, where four treatments were applied with doses of 2,0 L / ha for T2 2,5 L / ha for T3 3,0 L / ha for T4 and 3,5 L / ha for T5; also a T1 control. When evaluating the agronomic variables stem diameter, plant height, leaf length, number of leaves per plant and their yield, it was obtained that the best treatment of the evaluated variables was T5 (3,5 L / ha) which exceeded the rest of the treatments with yields of 4,5 kg myields of 4,5 kg m-2.significant differences, with yields of 4,5 kg m-2.